The Algerian Paraemia of the Aures: meaning, hidden meaning and discursive purpose - BOUZIDI, Boubakeur; BENDRIS, Imene (The Notebooks of the Algerian Poetics Laboratory Journal, 2022)
The aim of this study is to understand the meaning (explicit and/or implicit) of a corpus of Algerian paremia from the Aures region, to describe the semantic and inferential interpretation process shared by the speakers of this region and used in their daily language productions. To do this, we will attempt to present a semantic-pragmatic analysis of the collected corpus and to draw out the meaning, the hidden meaning (insinuated) and to present the discursive purpose of these proverbs.